Differential effect of classical and Lo-Fi background music on mathematics taks perfomance - Kistrianto, Ezekiel Tobias; Satiadarma, Monty; Subroto, Untung (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to examine the differential effects of classical background music (Mozart K.448) and lo-fi music on middle school students’ mathematics task performance. Method: A quasi-experimental design with repeated measures was employed involving 66 middle school students aged 12–15 years. Each participant completed a set of 20 standardized mathematics problems under three experimental conditions: silence (no music), classical background music (Mozart K.448), and lo-fi background music. The interventions were administered across separate sessions with a fixed time limit of 30 minutes per condition. Mathematics performance was assessed based on accuracy scores. Data analysis was conducted using repeated-measures analysis of variance (ANOVA), followed by Bonferroni post-hoc comparisons, while effect sizes were calculated to evaluate the magnitude of the observed differences. Findings: The results revealed a statistically significant difference in mathematics performance across the three conditions (F(2,122) = 8.459, p < .05). Classical background music produced the highest mean scores and was significantly more effective than the silence condition. In contrast, lo-fi music showed a modest increase in performance; however, this difference was not statistically significant. The effect size (partial η² = 0.122) indicates a moderate-to-large influence of background music on mathematical task performance. Significance: These findings suggest that background music does not exert uniform cognitive effects in academic contexts. Classical music, particularly Mozart K.448, appears to enhance cognitive focus and performance in mathematics tasks, whereas lo-fi music demonstrates limited cognitive benefit. The study provides empirical support for the selective use of auditory environments to optimize mathematics learning outcomes.